Design and optimization of a spectrometer for high-resolution SD-OCT. (22nd March 2019) - Wang, Lulu; Yu, Xiaojun; Ge, Xin; Wu, Xuan; Wang, Xianghong; Bo, En; Wang, Nanshuo; Liu, Xinyu; Ni, Guangming; Liu, Linbo
Abstract: We report the design of a high-efficiency spectrometer for high-resolution spectral-domain optical coherence tomography (SD-OCT). The advantages of the proposed spectrometer are two-fold: first, we use a concave mirror instead of a camera lens (as typically used) as the focusing optics to both improve the transmission efficiency and eliminate chromatic aberrations; second, the efficiency of the proposed spectrometer is approximately 1.23 times that of a refractive optics-based spectrometer for an SD-OCT system, with comparable ranging depth and axial resolution. Both theoretical analyses and imaging experiments were conducted to characterize and validate the performance of the proposed spectrometer.